2000
DOI: 10.1159/000029911
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of a Specific Leukotriene B<sub>4</sub> Receptor Antagonist (VML 295) on Blood Leukocytes, Cutaneous Inflammation and Epidermal Proliferation

Abstract: VML 295 (LY 293111) is a potent and specific leukotriene4 receptor antagonist. It has previously been shown in human volunteers that VML 295 at a dosage of 48 mg twice daily inhibits the ex vivo leukotriene B4 (LTB4)-induced upregulation of CD11b on peripheral blood neutrophils. A clear dose-response relatinship was shown. In addition, VML 295 inhibits various inflammatory aspects resulting from LTB4 challenge of the skin, again showing a dose-response relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…High-affinity LTB 4 receptors are on peripheral blood leukocytes as well as in the spleen and thymus, while low-affinity LTB 4 receptors are present on granulocytes and in the spleen [36]. The potent role of LTB 4 receptors in many different inflammatory diseases has led to the development of LTB 4 receptor antagonists as potential anti-inflammatory therapeutic treatments for pulmonary [37] and cutaneous [38][39][40] inflammatory states as well as immunosuppressive agents [41]. Such studies demonstrate that the LTB 4 receptor could be a potential target for therapeutic treatments for SMinduced skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…High-affinity LTB 4 receptors are on peripheral blood leukocytes as well as in the spleen and thymus, while low-affinity LTB 4 receptors are present on granulocytes and in the spleen [36]. The potent role of LTB 4 receptors in many different inflammatory diseases has led to the development of LTB 4 receptor antagonists as potential anti-inflammatory therapeutic treatments for pulmonary [37] and cutaneous [38][39][40] inflammatory states as well as immunosuppressive agents [41]. Such studies demonstrate that the LTB 4 receptor could be a potential target for therapeutic treatments for SMinduced skin injury.…”
Section: Discussionmentioning
confidence: 99%
“…LTB4R expression was observed to be increased in the proliferative zone of gastric epithelium [ 25 ]. Moreover, in a placebo controlled trial on human volunteers, the oral LTB4-receptor antagonist VML295 diminished the proliferative epidermal activity after traumatically induced skin lesions [ 26 ]. LTB4R showed an up-regulation in proliferative areas of esophageal mucosa as well, suggesting a role of this receptor for the proliferation of esophageal squamous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Moreover, it has been shown that VML 295 is able to block the ex vivo LTB 4 ‐induced CD11b upregulation on peripheral blood PMNs of healthy volunteers treated orally for 10 days, 28 , 30 and that there is a strong dose‐relationship with respect to these effects, with a maximum effect seen on a 200‐mg twice a day regimen. 31 Because of these very marked effects, a double‐blind randomized study in psoriatic patients was performed. 32 This study, in which patients with psoriasis were treated with VML 295 or placebo for 4 weeks, showed that VML 295 is a safe and well tolerated drug, with no evident side‐effects.…”
mentioning
confidence: 99%